Combustion products generated in simulated industrial fires. - Kirk, Katherine M.; Splawinski, Zenon; Bott, Raymond C.; Logan, Michael B. (Journal of Occupational & Environmental Hygiene)
Studies of firefighter exposure to combustion products have focused predominantly on real or simulated residential structure fires, with few investigations considering industrial fire scenarios. This study measured the atmospheric concentrations of a variety of volatile organic compounds (VOCs), acid gases, and polycyclic aromatic hydrocarbons (PAHs) produced during fires in simulated industrial premises, as well as the deposition of PAHs onto the structural firefighting ensembles worn by the firefighters involved in extinguishment activities. Ingress of these combustion products into the structural firefighting ensembles during firefighting was also measured. Benzene concentrations of up to 23 mg/m3 and total PAH concentrations ranging from 1.7 to 8.6 mg/m3 were observed in personal air samples collected outside the structural firefighting ensembles, as well as a variety of acid gases including hydrogen chloride and hydrogen cyanide. Most combustion products detected outside the structural firefighting ensembles were also detected inside the ensembles, although often at much lower concentrations. The degree of protection observed was not uniform across all the combustion products investigated, with lower levels of protection found for gaseous combustion products such as benzene, xylene, hydrogen cyanide, and hydrochloric acid as compared with PAHs. Deposition of a variety of PAH compounds was observed on the outer surface of the structural firefighting ensembles, with total PAH concentrations ranging from 161 to 347 ng/cm2. While similar combustion products are involved in firefighter exposures during residential and industrial fires, deposition rates of PAHs, may be substantially higher during industrial firefighting. This research provides evidence supporting fireground decontamination measures for management of contamination of structural firefighting ensembles and equipment worn or carried by firefighters during firefighting activities. Further research is required to investigate the potential for dermal deposition of PAHs during actual industrial fire responses, and characterize which stages of fire and firefighting operations contribute the most to firefighters' exposure to particular contaminants.